An AraC-Type Transcriptional Regulator Encoded on the Enterococcus faecalis Pathogenicity Island Contributes to Pathogenesis and Intracellular Macrophage Survival - Coburn, Phillip S. (American Society for Microbiology (ASM), 2008)
A gene encoding a putative AraC-type transcriptional regulator was identified on the 153-kb pathogenicity island (PAI) found among virulent Enterococcus faecalis strains. In an effort to understand the function of this regulator, designated PerA (for pathogenicity island-encoded regulator), we first examined the expression of the perA gene in the original PAI strain MMH594 and in an unrelated clinical isolate E99 by reverse transcription-PCR. Interestingly, expression analysis revealed no detectable perA transcript in MMH594, whereas a transcript was observed in strain E99. Nucleotide sequence analysis revealed that this altered expression between the two strains was attributable to the differential location of an IS1191 element within the putative promoter region upstream of the perA gene. In order to determine the role of this putative regulator in E. faecalis pathogenesis, a perA-deficient mutant was created in strain E99, and the wild-type and mutant pair were compared for phenotypic differences. In in vitro biofilm assays, the mutant strain showed a significantly higher level of growth medium-specific biofilm formation compared to the wild type. However, in a murine intraperitoneal infection model, the mutant strain was significantly less pathogenic. The mutant was also attenuated for survival within macrophages in vitro. These findings highlight the importance of PerA as a regulator of biofilm formation and survival within macrophages and is likely a regulator controlling determinants important to pathogenesis.